Strategic Planning Analysis to Realize an Integrated Financial Information System (Case Study: Pesantren Al-Ma'tuq Sukabumi) - Sayuti, Ahmad; H Suwiryo, Darmo; Rachmawati, Ike (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze strategic planning to realize an integrated financial information system in Pesantren Al-Ma'tuq Sukabumi. Through qualitative approaches and case studies, this study investigates the current state of financial management in Pesantren and identifies the main obstacles faced. The results of data analysis show that Al-Ma'tuq Islamic Boarding School faces challenges in fragmented financial management, with a financial management system that is not integrated, financial reporting processes that are carried out manually, and a lack of human resource competence. To overcome these obstacles, this study designed a strategic planning solution that aims to realize an integrated financial information system. This solution involves the application of good corporate governance principles to increase efficiency, transparency, and accountability in pesantren financial management. The results of this study are expected to provide a better understanding of the financial condition of pesantren and provide recommendations to pesantren managers, researchers, and the community to develop an integrated financial management system. In addition, this research is also expected to improve the quality of religious education and general education in pesantren and support the sustainability of pesantren in Indonesia.